Expression of adhesion molecules in leprosy lesions. - Sullivan, L (1991)
Leprosy presents as a clinical spectrum that is precisely paralleled by a spectrum of immunological reactivity. The disease provides a useful and accessible model, in this case in the skin, in which to study the dynamics of cellular immune responses to an infectious pathogen, including the role of adhesion molecules in those responses. In lesions characterized by strong delayed-type hypersensitivity against Mycobacterium leprae (tuberculoid, reversal reaction, and Mitsuda reaction), the overlying epidermis exhibited pronounced keratinocyte intracellular adhesion molecule 1 (ICAM-1) expression and contained lymphocytes expressing the ICAM-1 ligand, LFA-1. Conversely, in lesions in which delayed-type hypersensitivity was lacking (lepromatous), keratinocyte ICAM-1 expression was low and LFA-1+ lymphocytes were rare. Expression of these adhesion molecules on the cells within the dermal granulomas was equivalent throughout the spectrum of leprosy. The percentage of lymphocytes in these granulomas containing mRNA coding for gamma interferon and tumor necrosis factor alpha, synergistic regulators of ICAM-1 expression, paralleled epidermal ICAM-1 expression. In lesions of erythema nodosum leprosum, a reactional state of lepromatous leprosy thought to be due to immune complex deposition, keratinocyte ICAM-1 expression and gamma interferon mRNA+ cells were both prominent. Antibodies to LFA-1 and ICAM-1 blocked the response of both alpha beta and gamma delta T-cell clones in vitro to mycobacteria. Overall, the expression of adhesion molecules by immunocompetent epidermal cells, as well as the cytokines which regulate such expression, correlates with the outcome of the host response to infection.